2022
DOI: 10.1002/ece3.8550
|View full text |Cite
|
Sign up to set email alerts
|

The use of trail cameras to monitor species inhabiting artificial nest boxes

Abstract: Artificial boxes are commonly used in studies of cavity‐dwelling animals of various taxa. One advantage of nest boxes is that cameras can be used to monitor animals inside the cavity, however, most cameras used today have to be built de novo or modified or are expensive. Here, we describe a method for monitoring nest boxes using off‐the‐shelf models of trail cameras that can record photographs and videos in daylight and darkness (TCM; Trail Camera Method). The cameras can record sequentially within a given tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…However, the use of artificial cavities has a number of advantages over natural hollows, which are scarce in most managed forests. They provide unobstructed and quick access to the nest and eggs, the possibility to monitor broods 45 , and to manipulate physical factors, e.g., light or temperature 46 . Another limitation of our study is that it was performed during only one season.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of artificial cavities has a number of advantages over natural hollows, which are scarce in most managed forests. They provide unobstructed and quick access to the nest and eggs, the possibility to monitor broods 45 , and to manipulate physical factors, e.g., light or temperature 46 . Another limitation of our study is that it was performed during only one season.…”
Section: Discussionmentioning
confidence: 99%
“…By using shutters, we could make the boxes bright (with open shutters) or dark (with closed shutters). For more detailed information on the nest box construction, see 45 . In total, we analysed data from 14 dark and 18 bright nest boxes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also suggested that predator detection was likely underestimated, especially for partial predation or events involving small predators such as European weasels, which were less likely to trigger motion sensors on camera traps. These issues are common when quantifying avian nest predation [89][90][91].…”
Section: Advantages and Disadvantages Of Deep Nestboxesmentioning
confidence: 99%
“…A few studies have supplemented details on nest box dimensions (Arct et al, 2022;Cooper & Bonter, 2008;Maziarz et al, 2017;Zhang et al, 2021) and illustrations (Olah et al, 2014;Pasuwan et al, 2011;Stanback, 2020;Wimberger et al, 2017) as reference for future studies of species. While most nest boxes were built with a single chamber, some studies may include additional chambers apart from the nest chamber to place monitoring equipment [e.g., camera surveillance system or camera traps; see Surmacki and Podkowa (2022) and Zárybnická et al (2016)]. Most nest boxes were constructed from wood material (Arct et al, 2022;Miller, 2002;Palko et al, 2011;Zhang et al, 2021), while others were from other non-wood materials (Beasley & Parrish, 2009;Olah et al, 2014).…”
Section: Introductionmentioning
confidence: 99%